2009
DOI: 10.1016/j.cub.2008.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Ants Learn Geometry and Features

Abstract: Rats trained to relocate a particular corner in a rectangular arena systematically confound the correct corner and the diametrically opposite one--this rotational error demonstrates the use of the geometry of space (i.e., the spatial arrangement of the different components of a visual scene). In many cases, geometric information is preferentially used over other spatial cues, suggesting the presence of a dedicated geometric module located in the parahippocampus and processing only geometric information. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 29 publications
7
104
2
Order By: Relevance
“…Thus, as shown for many other animals in similar experimental environments (e.g. Cheng, 1986;Kelly & Spetch, 2001;Sovrano, Bisazza, & Vallortigara, 2002;Wystrach & Beugnon, 2009), including recently for bumblebees in a different and five times smaller box (Sovrano et al, , 2013, bees also made rotational errors in our rectangular box. Note that bees did not always land in the corner where they first crossed the decision line.…”
Section: Bees Confuse the Diagonally Opposite Cornerssupporting
confidence: 77%
See 3 more Smart Citations
“…Thus, as shown for many other animals in similar experimental environments (e.g. Cheng, 1986;Kelly & Spetch, 2001;Sovrano, Bisazza, & Vallortigara, 2002;Wystrach & Beugnon, 2009), including recently for bumblebees in a different and five times smaller box (Sovrano et al, , 2013, bees also made rotational errors in our rectangular box. Note that bees did not always land in the corner where they first crossed the decision line.…”
Section: Bees Confuse the Diagonally Opposite Cornerssupporting
confidence: 77%
“…In recent years, model simulations and behavioural experiments in ants have shown that rotational errors in rectangular arenas can be parsimoniously explained by view-based strategies without explicit representation of geometry Wystrach et al, 2011;Wystrach & Beugnon, 2009). The choice behaviour of the bees in our experimental set-up agrees very well with a simple image-matching model (see Fig.…”
Section: Bees Rely Predominantly On Pictorial Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…All species which have been investigated appear to mistake the target location with this rotationally equivalent position (reviewed in Vallortigara, 2009a). Very recently, even ants (Gigantiops destructor) have been proven capable of reorienting in a rectangular enclosure, displaying the same rotational errors of vertebrate species (Wystrach & Beugnon, 2009). The authors of this last study explained their findings within a view-based matching strategy, arguing that ants would match a view-based representation, stored and captured while moving, to the current view without encoding any geometry.…”
Section: Geometrymentioning
confidence: 99%